The Prevalence of Extended-Spectrum β-lactamase (ESBL) and Carbapenem-Resistant Enterobacteriaceae (CRE) Isolates in Positive Blood Cultures of Patients in A Teaching Hospital in Kuwait Over A 2-year Period. (4th October 2017) - Taqi, Muna; Jamal, Wafaa; Rotimi, Vincent
Abstract: Background: Extended spectrum β-lactamase (ESBL)-producing organisms and carbapenem resistant Enterobacteriaceae (CRE) pose unique challenges to clinical microbiologists, infectious diseases physicians, infection control professionals and antibacterial-discovery scientists. This study was undertaken to determine the prevalence of extended-spectrum β-lactamase (ESBL)-producing and carbapenemase-positive members of the family Enterobacteriaceae isolated from positive blood cultures of patients in our hospital. Methods: Enterobacteriaceae isolates from proven cases of blood stream infections (BSI) from January 2014 to December 2015 were included in the study. They were identified and tested for their susceptibilities to 18 antibiotics by conventional methods and semi-automated VITEK-2 system. ESBL and carbapenem resistance (CR) were detected by phenotypic and molecular PCR methods, and characterized by sequencing. Results: A total of 4133 blood cultures were positive. Of these, 543 (13.1%) were positive for Enterobacteriaceae, 135 (24.9%) of which were ESBL producers and 28 (5.2%) identified as CRE. The most common of the ESBL-producing isolates were Escherichia coli (81:60%) and Klebsiella pneumoniae (44:32.6%). Resistance rates of E. coli to the cephalosporins ranged from 47–100%, ciprofloxacin 70.4%, imipenem 2.5% and meropenem 1.2%. Higher proportions of K. pneumoniae were resistant to the cephalosporins (68.2–100%), imipenem (27.3%) and meropenem (22.7%). Sequence analysis of the ESBL revealed CTX-M-15 as the commonest enzyme (75%). The CRE harbored mainly the VIM (28.6%) and NDM-1 (35.7%) genes. Conclusion: Our study demonstrates a high prevalence of ESBL-producing Enterobacteriaceae isolates of the CTX-M-15 variety and equally high prevalence of CRE, predominantly VIM and NDM-1 producers, among blood culture isolates at our hospital. Disclosures: All authors: No reported disclosures.